Pengaruh Work-Life Balance, Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Pegawai di Sekretariat Dewan Perwakilan Rakyat Daerah Kabupaten Sragen - Malika Berthy Santoso; Asih Handayani (Lembaga Yasin AlSys, 2026)
The suboptimal performance of employees at the Secretariat of the Regional People’s Representative Council of Sragen Regency is indicated by performance achievements that have not met the targets and the persistence of work discipline problems. This study aims to analyze the effects of work-life balance, work environment, and work discipline on the performance of employees at the Secretariat of the Regional People’s Representative Council of Sragen Regency. This study employed a quantitative approach involving all 44 civil servants at the Secretariat of the Regional People’s Representative Council of Sragen Regency, who were selected using a saturated sampling or census technique. Data were collected using questionnaires and analyzed through validity, reliability, classical assumption, multiple linear regression, t-test, F-test, and coefficient of determination (R²) analyses. The results show that work-life balance has a significant effect on employee performance (p = 0.000 < 0.05), whereas the work environment has no significant effect on employee performance (p = 0.728 > 0.05). Work discipline also has a significant effect on employee performance (p = 0.036 < 0.05). The regression model was deemed appropriate for use, with work-life balance, work environment, and work discipline jointly explaining 40.6% of the variance in employee performance. This study concludes that improvements in employee performance are primarily determined by work-life balance and work discipline. These findings imply that the institution needs to manage workloads and working hours effectively and strengthen employee discipline to support the achievement of optimal performance.